2020
DOI: 10.3390/su12166486
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve Sustainability Competences of Teacher Training? Inquiring the Prior Knowledge on Climate Change in Primary School Students

Abstract: The work is carried out in accordance with the Sustainable Development Goal 13 Climate Action with prospective primary school teachers. The study presented is part of the science education subject at the University of Seville (Spain) during the 2019–2020 academic year. This research has two main goals, on the one hand, to present an innovative educational experience (design and implementation) for teacher training, on the other hand, to assess the educational implication of the experience from the prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…Currently, there are a number of tools that have been developed in order to measure competencies related to sustainability. Internationally, there is the Sustainability Literacy Test (the SuLiTest) [43] and the Sustainability Consciousness Questionnaire [44], while in Spain we have the Self-perception Skills in Sustainability (SQSS) [45] questionnaire. A literature review of the tools used to evaluate sustainability competencies indicated that, among these tools, there is an overrepresentation of the evaluation methodology based on self-assessment questionnaires [41].…”
Section: Evaluating Sustainability Competenciesmentioning
confidence: 99%
“…Currently, there are a number of tools that have been developed in order to measure competencies related to sustainability. Internationally, there is the Sustainability Literacy Test (the SuLiTest) [43] and the Sustainability Consciousness Questionnaire [44], while in Spain we have the Self-perception Skills in Sustainability (SQSS) [45] questionnaire. A literature review of the tools used to evaluate sustainability competencies indicated that, among these tools, there is an overrepresentation of the evaluation methodology based on self-assessment questionnaires [41].…”
Section: Evaluating Sustainability Competenciesmentioning
confidence: 99%
“…The use of these open access digital tools, through mobile devices, provides students with a positive, innovative, and current image of education [72], and allows information to be collected in an efficient and effective manner [73]. The questionnaires were completed at two moments-before (pre-test) and after the outdoor experience (post-test)-like other similar studies [12,74].…”
Section: Category System: Assess Ecpt's Self-perceptionmentioning
confidence: 99%
“…The scholarly literature describes the recent developments in school reforms regarding sustainability issues. For example Solís-Espallargas and Morón-Monge describe how to improve sustainability competences of teacher training on the basis of inquiring [40]. Morón-Monge et al present an approach to prospective primary school teachers' concepts of environment and biodiversity through their design of educational itineraries [41].…”
mentioning
confidence: 99%
“…We claim that each stage should be associated with a corresponding approach to climate education. Climate education should not only concentrate on knowledge development but, first of all, should shape the value system and an ability to take actions to benefit the climate [40][41][42][43][44][45][46][47][48][61][62][63][64]83,[89][90][91]. Our conceptual model postulates that the systemic change in education should reflect these four stages.…”
mentioning
confidence: 99%
See 1 more Smart Citation